2004
DOI: 10.1002/jssc.200301599
|View full text |Cite
|
Sign up to set email alerts
|

Determination of betulin in Grewia tiliaefolia by HPTLC

Abstract: A sensitive, rapid, simple, and accurate high performance thin layer chromatographic method has been developed to standardize the bark of Grewia tiliaefolia Vahl. (Family: Tiliaceae) using betulin as an analytical marker. Chloroform extracts of bark from five different sources were used for HPTLC on silica gel with toluene-ethyl acetate, 90 + 10 v/v, as mobile phase. Under these conditions, the Rf of betulin was 0.22. The calibration plot was linear in the range of 1000 ng to 1800 ng of betulin and the correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…For instance, the bark extract of the plant possess hepatoprotective effect against CCl 4 induced toxicity in rats and the two isolated constituents D-erythro-2-hexenoic acid γ-lactone (EHGL) and Gulonic acid γ-lactone (GAGL) showed strong antioxidant activities against free radicals 6 . In addition, the bark of the plant contain high amount of lupeol and betulin, which are the pharmacologically active triterpenoids demonstrated to possess a wide range of medicinal properties including anticancer effects 7 . Regarding the safety, recently our group have demonstrated that the methanolic leaf extract of GT is safe and non-toxic, when analysed using both in vitro and in vivo experimental models 8 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the bark extract of the plant possess hepatoprotective effect against CCl 4 induced toxicity in rats and the two isolated constituents D-erythro-2-hexenoic acid γ-lactone (EHGL) and Gulonic acid γ-lactone (GAGL) showed strong antioxidant activities against free radicals 6 . In addition, the bark of the plant contain high amount of lupeol and betulin, which are the pharmacologically active triterpenoids demonstrated to possess a wide range of medicinal properties including anticancer effects 7 . Regarding the safety, recently our group have demonstrated that the methanolic leaf extract of GT is safe and non-toxic, when analysed using both in vitro and in vivo experimental models 8 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, some analytical methods have been reported on the analysis of the various bioactive ingredients in the birch bark, including betulin, betulinic acid by HPLC or GC-MS. Analysis of betulin in Grewia tiliaefolia by HPTLC method has been described [6]. Betulinic acid has been determined by HPLC in Doliocarpus schottianus and by GC-MS after derivatisation in Platanus acerifolia and in Betula pendula [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Lupeol, a triterpene compound has been isolated from Crataeva nurvala by HPTLC and also showed antioxaluric and anticalciuric effects in rats against hydroxyprolineinduced hyperoxaluria [34]. The earlier investigators isolated lupeol from the methanol extract of stem bark of Grewia titiaefolia and evaluated the cytotoxic properties on in vitro cell lines [35]. Recently, the isolation of andrographolide, 14-deoxyandrographolide, 14-deoxy-12-hydroxyandrographolide, β-sitosterol, stigmasterol and chlorophyll a, β-sitosterol, stigmasterol, 5,2'-dihydroxy-7,8-dimethoxyflavone, long chain transcinnamateesters and β-sitosteryl fatty acid esters, β-sitosterol,monogalactosyl diacylglycerols, lupeol, and triacylglycerols from the pods; and 14-deoxy andrographolide of A. paniculata [36].…”
Section: Discussionmentioning
confidence: 99%
“…The dried extracts were separately redissolved in 1 ml of methanol and sample of varying concentration (1-5 µl) for lupeol were spotted for quantification. 1 mg of standard lupeol was prepared in 1 ml of chloroform, and different amounts of (5000-10000 ng) lupeol were loaded onto a TLC plate to get the calibration curve [19][20][21][22].…”
Section: Thin Layer Chromatographymentioning
confidence: 99%